ANALISIS KOMPORASI TINGKAT PENGEMBALIAN, RISIKO DAN KOEFISIEN VARIASI PADA SAHAM SYARIAH DAN SAHAM KONVENSIONAL DI LQ45 - Haanurat, Ifayani; Razak, Linda Arisanty; Awaliah, Eni Versary (Jurnal Ar-Ribh, 2021)
This study aims to examine the comparison of returns, risks and coefficient of variation in sharia and conventional companies in LQ45. The sample collection method uses the Purpose Sampling method, namely the selection of samples based on certain criteria so that each of the 4 Islamic and conventional shares is obtained. The technique used is the independent sample T test. Based on the results of the study indicate that there is no significant difference between the rate of return, risk and coefficient of variation in Islamic and conventional companies in LQ45Keywords: Returns, Risk, Variation Coefficient, Sharia Shares, Conventional Shares, LQ 45